Agronomical selection on loss‐of‐function of GIGANTEA simultaneously facilitates soybean salt tolerance and early maturity. Issue 10 (6th September 2022) - Dong, Lidong; Hou, Zhihong; Li, Haiyang; Li, Zhaobo; Fang, Chao; Kong, Lingping; Li, Yongli; Du, Hao; Li, Tai; Wang, Lingshuang; He, Milan; Zhao, Xiaohui; et al.
ABSTRACT: Salt stress and flowering time are major factors limiting geographic adaptation and yield productivity in soybean ( Glycine max ). Although improving crop salt tolerance and latitude adaptation are essential for efficient agricultural production, whether and how these two traits are integrated remains largely unknown. Here, we used a genome‐wide association study to identify a major salt‐tolerance locus controlled by E2, an ortholog of Arabidopsis thaliana GIGANTEA ( GI ). Loss of E2 function not only shortened flowering time and maturity, but also enhanced salt‐tolerance in soybean. E2 delayed soybean flowering by enhancing the transcription of the core flowering suppressor gene E1, thereby repressing Flowering Locus T ( FT ) expression. An E2 knockout mutant e2 CR displayed reduced accumulation of reactive oxygen species (ROS) during the response to salt stress by releasing peroxidase, which functions in ROS scavenging to avoid cytotoxicity. Evolutionary and population genetic analyses also suggested that loss‐of‐function e2 alleles have been artificially selected during breeding for soybean adaptation to high‐latitude regions with greater salt stress. Our findings provide insights into the coupled selection for adaptation to both latitude and salt stress in soybean; and offer an ideal target for molecular breeding of early‐maturing and salt‐tolerant cultivars. Abstract : In soybean, a single e2 allele not only shortens flowering time and maturity but also enhances salt tolerance by regulating distinct molecular networks. Loss‐of‐function e2 alleles have undergone a coupled selection process between the early maturity and salt stress tolerance traits in soybean.